The mediating role of strategic planning awareness in the impact of organizational innovation on business excellence in hospitals - EKİZ KAVUKOĞLU, TUTKU; İŞCİ, EMRE (My University, 2023)
Purpose: Evaluating the operational outcomes of hospitals is critical concerns for hospital managers. The realization of these evaluations through the principles of Total Quality Management (TQM) is important so that decision-makers can base their decisions on rational grounds. To achieve TQM principles, hospitals need innovative processes that can adapt to changing patient expectations. Innovation activities that will lead to business excellence can be achieved with the strategic planning awareness of healthcare professionals. In this study, it is aimed to evaluate the effect of organizational innovation on business excellence and to reveal the role of strategic planning awareness in this relationship in hospitals. Design/methodology/approach: The data were collected using a quantitative questionnaire to 450 healthcare professionals working in private hospitals operating in Istanbul (Turkey). The data were analyzed using the AMOS (Analysis of Moment Structures) 23.0 and SPSS (Statistical Package for the Social Sciences) for Windows 25.0 program. In addition to the reliability analysis, confirmatory factor analysis was performed using the AMOS program to test the construct validity of the scales. The model established in line with the research hypotheses was tested with path analysis and mediator role analysis. Findings: The results confirm that organizational innovation has a statistically significant and positive effect on strategic planning awareness and business excellence. In addition, it has been determined that strategic planning awareness has a statistically significant and positive effect on business excellence. Moreover, the research model confirms that strategic planning awareness plays a mediating role in the relationship between organizational innovation and business excellence. Research limitations/implications: The limitation of the study is that it was conducted only in private hospitals. A comparative study that includes the public health sector can further strengthen the research framework. Practical implications: Hospitals that invest in innovative activities can get the reward of their efforts as business excellence. However, this is affected by the strategic planning awareness of healthcare professionals. Research results present the role of strategic planning awareness on the way to business excellence led by organizational innovation. Achieving business excellence in complex and constantly changing environmental conditions depends on an appropriate strategic plan for hospitals. In order to achieve these goals included in the strategic plans, the education of healthcare professionals that contributes to their strategic perspectives should be supported and their participation in decision-making processes should be ensured. Originality/value: The research contributes to the literature on the relationship between organizational innovation and business excellence in the health sector. In addition, revealing the role of strategic planning awareness of healthcare professionals in this relationship is the originality of the research. In addition, the research supports the literature that allows performance evaluation in hospitals to be carried out with a business excellence model based on TQM.
Keywords: Sosyal ve Beşeri Bilimler; Çalışma Ekonomisi ve Endüstri ilişkileri; Yönetim ve Çalışma Psikolojisi; İşletme; Social Sciences and Humanities; Labor Economics and Industrial Relations; Management and Industrial Psychology; Management; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Genel Karar Bilimleri; Sosyal Bilimler ve Beşeri Bilimler; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Strateji ve Yönetim; General Decision Sciences; Social Sciences & Humanities; Business and International Management; General Business, Management and Accounting; Strategy and Management; Business excellence; Hospitals; Innovation; Strategic planning; Strategic planning awareness